Oilseed-legume intercropping is productive and profitable in low input scenarios. (January 2023) - Dowling, Alyce; Roberts, Penny; Doolette, Ashlea; Zhou, Yi; Denton, Matthew D.
Abstract: CONTEXT: The cost of fertiliser and fungicide is rising rapidly, increasing farmers' financial risk and reducing gross margins. By utilising the synergistic interspecies interactions that increase system resource efficiency and provide a buffer against disease, oilseed-legume intercropping may provide an opportunity to allow farmers to maintain yield while reducing these input costs. OBJECTIVE: To investigate the effect of varying fertiliser and fungicide inputs on the yield efficacy and economics of chickpea-linseed and chickpea-canola intercrops in mechanised broadacre systems in a Mediterranean climate. METHODS: The oilseed species linseed ( Linum usitarissimum L.) and canola ( Brassica napus L.) were intercropped with Kabuli chickpea ( Cicer arietinum L.) in a double skip row arrangement under varying fertiliser and fungicide regimes. These intercrops were compared with their respective sole crops for land use efficiency and economic productivity. RESULTS and CONCLUSIONS: The land equivalency ratio (LER) of the intercrop under nil fertilisation averaged 1.04 compared with 0.94 under high fertilisation. The LER of the intercrops under nil fungicide averaged 1.39 compared with 0.93 under high fungicide. Intercropping provided gross margin stability across environments, while the gross margins of the sole crops varied depending on environment, a pattern which held even when grain prices and input costs varied. In summary, the greatest intercrop land use and economic benefit occurred in the low input treatments. SIGNIFICANCE: The overyielding and high gross margins of the low input intercrops suggest that oilseed-legume intercropping may have potential as a profitable lower risk alternative to traditional high input monocultures in a Mediterranean climate. Graphical abstract: Unlabelled Image Highlights: The cost of synthetic inputs in broadacre cropping systems is rising, increasing farmers' financial risk and reducing profit. Examined oilseed-legume intercropping as a cost-saving strategy in mechanised broadacre systems in a Mediterranean climate. Low input fertiliser and fungicide treatments had the greatest intercrop benefit. Low input intercrop treatments reduced financial risk and improved yield stability. Oilseed-legume intercrops have potential as a profitable alternative to traditional high input monocultures.